ADAPTATION OF THE DECISIONAL BALANCE SCALE FOR SEXUAL ABSTINENCE AND THE SELF-EFFICACY SCALE FOR SEXUAL ABSTINENCE TO TURKISH: A VALIDITY AND RELIABILITY STUDY - BEYHAN, ABDULLAH; ERGÜN, AYŞE (My University, 2020)
The aim of this study is to make Turkish adaptation and psychometric analysis of the Decisional Balance Scale for Sexual Abstinence (DBSSA) and Self-Efficacy Scale for Sexual Abstinence (SESSA) developed in line with the Transtheoretical Model (TTM). DBSSA and SESSA were administered to total of 482 students, and 50 students were retested two weeks later. The validity of the scale was evaluated by; factor analysis, content and construct validity analysis while reliability was evaluated by internal consistency and test-retest. While content validity of scale was evaluated by receiving opinions from 12 experts, internal consistency, item analysis and test-retest results were evaluated via Cronbach alpha reliability coefficient and Pearson correlation analysis, respectively. The DBSSA content validity index was found as 0.97 and the SESSA content validity index was found as 1, and it was determined that there was a consensus among experts. Cronbach alpha reliability coefficient was found to be; 0,61 for pros/internal, 0.77 for pros/external, and 0.76 for cons among DBSSA subscales, while 0.88 for the SESSA. The test-retest reliability correlation was 0.70 for pros/internal, 0.70 for pros/external, and 0.80 for cons while 0.85 for SESSA. DBSSA and SESSA were found to be suitable, valid and reliable for Turkish culture.

Bu çalışmanın amacı Transteoretik Model (TTM) doğrultusunda geliştirilmiş Cinsellikten Kaçınma Karar Dengesi Ölçeği (CK-KDÖ) ve Cinsellikten Kaçınma Öz Yeterlilik Ölçeği’nin (CK-ÖYÖ) Türkçe uyarlamasını ve psikometrik analizlerini yapmaktır. CK-KDÖ ve CK-ÖYÖ’leri toplam 482 öğrenciye uygulanıp iki hafta sonra 50 öğrenciye tekrar test yapıldı. Ölçeğin geçerliği; faktör analizi, kapsam ve yapı geçerliği analizleri ile değerlendirilirken, güvenirliği ise iç tutarlılık ve test-tekrar test yöntemleri ile değerlendirildi. Ölçeğin kapsam geçerliği 12 uzmanın görüşü alınarak değerlendirilirken, iç tutarlılığı, madde analizi ve test-tekrar test sonuçları sırası ile Cronbach alfa güvenirlik katsayısı ve Pearson korelasyon analizi ile değerlendirildi. CK-KDÖ kapsam geçerliği indeksi 0.97 ve CK-ÖYÖ kapsam geçerliği indeksi 1 bulundu, ve uzmanlar arası görüş birliği olduğu belirlendi. Cronbach alfa güvenirlik katsayısı; CK-KDÖ alt boyutlarından içsel yarar algısı için 0.61, dışsal yarar algısı için 0.77 ve zarar algısı için 0.76; CK-ÖYÖ için ise 0,88 bulundu. Test-tekrar test güvenirlik korelasyonu; içsel yarar algısı için 0.70, dışsal yarar algısı için 0.70 ve zarar algısı için 0.80; CK-ÖYÖ için ise 0.85 bulundu. CK-KDÖ ve CK-ÖYÖ Türk kültürü için uygun, geçerli ve güvenilir bulundu.
Cinsellikten Kaçınma Karar Dengesi Ölçeği ve Cinsellikten Kaçınma Öz Yeterlilik Ölçeğinin Türkçe Uyarlaması: Geçerlik ve Güvenirlik Çalışması